Severe exercise-induced anaphylaxis in a hot and humid area successfully treated with omalizumab: a case report - Mobayed, Hassan; Al-Nesf, Maryam Ali; Robles-Velasco, Karla; Cherrez-Ojeda, Ivan; Ensina, Luis Felipe; Maurer, Marcus (Frontiers in Allergy, 2023)
Exercise-induced anaphylaxis (EIA) is a rare disorder in which anaphylaxis occurs exclusively after physical activity. Here, we report a case of severe EIA where anaphylaxis was initially only induced by strenuous exercise. Suddenly the anaphylaxis got out of control to the degree that usual daily activities triggered it. Exposure to a hot and humid environment appeared to be a cofactor for the development of severe symptoms resistant to usual preventive measures. Treatment with omalizumab (anti-IgE) was initiated and resulted in marked improvement. We discuss unique aspects of this case in comparison to published information on the clinical features, triggering cofactors, diagnosis, and treatment of EIA.